Peran LAZISMU (Lembaga Amil Zakat, Infaq, dan Sadaqah Muhammadiyah) dalam Upaya Mengurangi Tingkat Kemiskinan Masyarakat Kota Tangerang - Dwi Arifah, Wahyu Aryani; Kurniawan, Danang; Yusro, M (Masterpiece: Journal of Islamic Studies and Social Sciences, 2024)
Poverty is characterized by a lack of property and income, resulting in the inability to fulfill basic human needs such as food, a home, and clothing. The aim of this research is to determine the role of the Amir Zakat Infaq and Almus Muhammadiyah institutions in effort to reduce poverty in Tangerang City. Qualitative methods were used to analyze data obtained from interviews with LazisMu administrators were used for data mining procedures. The data analysis process includes data collection, reduction, presentation, and validation. From the search results, the first ZIS fund collection mechanism used by LazisMu Tangerang City was based on recommendations from people closest to the Mustahik candidates, while the second mechanism worked together with branch managers to collect data on Mustahiks. After collecting and registering mustahik candidates, the program department conducts a study by considering the special circumstances of mustahik candidates. Based on the research results the funds collected by LazisMu were distributed to various structured programs, including education, economy, health, social, da'wah, and other activities. - Kemiskinan ditandai dengan kurangnya harta benda dan pendapatan, sehingga mengakibatkan ketidakmampuan memenuhi kebutuhan dasar manusia seperti sandang, pangan, dan papan. Tujuan penelitian ini adalah untuk mengetahui peran lembaga Amir Zakat Infaq Muhammadiyah dalam upaya mengurangi kemiskinan di kota Tangerang. Metode kualitatif digunakan untuk menganalisis data yang diperoleh dari wawancara dengan pengurus LAZISMU. Proses analisis data meliputi pengumpulan, reduksi, penyajian, dan validasi data. Dari hasil penelusuran, mekanisme pengumpulan dana ZIS pertama yang digunakan LAZISMU Kota Tangerang berdasarkan rekomendasi orang-orang terdekat calon Mustahik, sedangkan mekanisme kedua bekerja sama dengan pengelola cabang untuk mendata para Mustahik. Setelah mengumpulkan dan mendata calon mustahik, bagian program melakukan kajian dengan mempertimbangkan keadaan khusus calon mustahik. Berdasarkan hasil penelitian, dana yang berhasil dihimpun LazisMu disalurkan ke berbagai program pendidikan, ekonomi, Kesehatan, sosial, dakwah, dan kegiatan lainnya.